Comparison of olfactory function between neuromyelitis optica and multiple sclerosis. (3rd August 2018) - Li, Li-Min; Guo, Hui-Yue; Zhao, Ning; Zhang, Lin-Jie; Zhang, Ningnannan; Liu, Jingchun; Yang, Li
ABSTRACT: Objectives: Olfactory dysfunction (ODF) has been reported in patients with neuromyelitis optica (NMO) and multiple sclerosis (MS). However, the comparison of olfactory function and olfactory-related gray matter (GM) between patients with NMO and MS needed to be further elucidated. Materials and methods: Thirty-seven patients with NMO and 37 with MS were enrolled. Olfactory function was evaluated with a Japanese T&T olfactometer test kit, and the neuroanatomical features of olfactory-related GM were assessed using voxel-based morphometry. Results: Olfactory deficits were found in 51.4% of patients with NMO and 40.5% of patients with MS. Patients with NMO with ODF had significantly smaller olfactory bulbs than patients with MS with ODF ( p = 0.031). Olfactory-related GM atrophy was found in patients with NMO in several regions of the right orbitofrontal cortex and right superior frontal gyrus; in patients with MS, reduced GM volume was found in the right parahippocampal gyrus and piriform cortex ( p < 0.05, cluster size > 200 voxels). Conclusions: Olfactory deficits are common in both NMO and MS. However, the neuroanatomical features related to olfactory deficits differ greatly between the two diseases.